Physico-chemical Characterization and Antibacterial Activity of Ozonated Pomegranate Seeds Oil - Amri, Zahra; Ben Hamida, Sarra; Dbeibia, Amal; Ghorbel, Asma; Mahdhi, Abdelkarim; Znati, Mansour; Ambat, Indu; Haapaniemi, Esa; Sillanpää, Mika; Hammami, Mohamed (Ozone: science & engineering, 2020)
The aim of this study is to evaluate the quality index, functional groups changes, and antimicrobial activity of ozonized pomegranate seeds oil (OPSO). Results have shown that peroxide and acidity values were increased with ozonation times. The FT-IR and 1 H NMR analyses of oil samples have confirmed chain scission at C = C bonds of the fatty acid chains during ozonation and the formation of new carbonyl compounds such as aldehyde, 1,2,4-trioxolane. The ozonation reaction improves the antibacterial activity of non-ozonized PSO. These results make an open door to new applications of OPSO.